Surgical Treatment of Neuroendocrine Liver Metastases - Ser Yee Lee; Peng Chung Cheow; Jin Yao Teo; London L. P. J. Ooi (International Journal of Hepatology)
Management of Neuroendocrine liver metastases (NELM) is challenging. The presence of NELM worsens survival outcome and almost 10% of all liver metastases are neuroendocrine in origin. There is no firm consensus on the optimal treatment strategy for NELM. A systematic search of the PubMed database was performed from 1995–2010, to collate the current evidence and formulate a sound management algorithm. There are 22 case series with a total of 793 patients who had undergone surgery for NELM. The overall survival ranges from 46–86% at 5 years, 35–79% at 10 years, and the median survival ranges from 52–123 months. After successful cytoreductive surgery, the mean duration of symptom reduction is between 16–26 months, and the 5-year recurrence/progression rate ranges from 59–76%. Five studies evaluated the efficacy of a combination cytoreductive strategy reporting survival rate of ranging from 83% at 3 years to 50% at 10 years. To date, there is no level 1 evidence comparing surgery versus other liver-directed treatment options for NELM. An aggressive surgical approach, including combination with additional liver-directed procedures is recommended as it leads to long-term survival, significant long-term palliation, and a good quality of life. A multidisciplinary approach should be established as the platform for decision making.